Testing the equality of Nifty 50 stocks' volatility risk using correlated F-ratio. (3rd October 2022) - Jayakumar, G.S. David Sam; Samuel, W.; Sulthan, A.
This article introduces a modified version of rescaling the scale and shape parameters of McKay's bivariate gamma distribution and this considered to be the McKay's bivariate chi-square distribution (MBCHSQD). The marginals are univariate chi-square distribution with different degrees of freedom. Furthermore, conditional distributions and constants of the conditionals, generating functions are also derived. The distribution of correlated F-ratio is derived and the percentage points are computed at 5% and 1% level. Two-dimensional smooth curves are used to visualise the shape of derived densities graphically. The proposed F-distribution is applied in testing the equality of variances between two correlated Nifty 50 stocks when the Government of India in 2016 announced the scheme of demonetisation, in which the financial institutions with diverse industrial background in India got affected. Therefore, in order to test the equality of variance, the returns of Nifty 50 stocks are considered during pre and post-demonetisation periods in India.